Improving the Competitiveness of Peanut Chip MSMEs through Logo Rebranding and Product Innovation “PICA” - Halimatus Sa'diyah; Astri Puji Nur Rohma; Lisa Febriana Sutikno; Nonni Yap; Evi Dwi Kartikasari (Pascasarjana Universitas Mataram, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in Indonesia’s economic development; however, many food-based MSMEs face competitiveness challenges due to limited product differentiation, weak brand identity, and inadequate marketing strategies. This community service program aimed to enhance the competitiveness of a peanut chip MSME through integrated product innovation, logo rebranding, marketable packaging design, and digital marketing optimization under the brand “PICA” (Rich-Flavored Peanut Chips). The program was implemented through several stages, including field observation and problem analysis, product formulation and processing trials, visual identity redesign, packaging development, digital promotional media creation, and monitoring and evaluation. Product innovation focused on transforming conventional fried peanuts into thin, crispy peanut chips with multiple flavor variants to increase sensory appeal and market differentiation. Rebranding activities involved redesigning the logo, selecting appropriate color schemes and typography, and creating a consistent brand identity aligned with modern consumer preferences. Packaging was upgraded from simple transparent plastic to premium standing pouches with informative and visually attractive labels to improve product perception and shelf competitiveness. In addition, digital marketing was strengthened through the use of Instagram and WhatsApp Business to expand market reach and enhance consumer engagement. The results demonstrated improvements in product quality, visual attractiveness, brand recognition, and promotional effectiveness. Overall, the integration of product innovation, rebranding, marketable packaging, and digital marketing proved effective in increasing the competitiveness and growth potential of peanut chip MSMEs. This program highlights the importance of comprehensive innovation strategies in supporting sustainable MSME development in the increasingly competitive food industry.